The role of women in work and society in the Ancient Near East - Lion, Brigitte; Michel, Cécile (Studies in ancient Near Eastern records, 2016)
Women and work in the ancient Near East : an introduction / Brigitte Lion and Cécile Michel -- Weaving, potting, churning : women at work during the Uruk Period : evidence from the cylinder seals / Catherine Breniquet -- Representation of women in Mesopotamian lexical lists / Camille Lecompte -- Women and land in the Presargonic Laga corpus / Fumi Karahashi -- The role of women in work and society in the Ebla Kingdom (Syria, 24th century BC) / Maria Giovanna Biga -- Women and production in Sargonic Adab / Massimo Maiocchi -- Professional women and women at work in Mesopotamia and Syria (3rd and early 2nd millennia BC) : the (rare) information from visual images / Adelheid Otto -- Women at work and women in economy and society during the Neo-Sumerian Period / Bertrand Lafont -- The sex-based division of work versus intersectionality : some strategies for engendering the Ur III textile work force / Agnès Garcia-Ventura -- Women work, men are professionals in the Old Assyrian archives / Cécile Michel -- The job of sex : the social and economic role of prostitutes in ancient Mesopotamia / Jerrold S. Cooper -- "She is not fit for womanhood" : the ideal housewife according to Sumerian literary texts / Jana Matuszak -- Economic activities of Naditum-women of "ama" reflected in the field sale contracts (Mhet II/1-6) / Ichiro Nakata -- Cherchez la femme! : the economic role of women in Old Babylonian Sippar / Katrien de Graef -- Economic activities of women according to Mari texts (18th century BC) / Nele Ziegler -- Women at work in Mesopotamia : an attempt at a legal perspective / Sophie Démare-Lafont -- Sources for the study of the role of women in the Hittite administration / Matteo Vigo -- Work and gender in Nuzi society / Brigitte Lion -- Women in economic agreements : Emarite sale contracts (Syria, 13th century BC) / Josué J. Justel -- The kubuddau-gift in the Emar texts / Masamichi Yamada -- Women in Elamite royal inscriptions : some observations / Eiko Matsushima -- Women and their activities in divinatory texts / Virginie Muller -- Studying gender : a case study of female administrators in Neo-Assyrian palaces / Saana Svärd -- Historiography on studies dedicated to women and economy during the Neo-Babylonian period / Francis Joannès -- Invisible workers : the role of women in textile production during the 1st millennium BC / Louise Quillien -- Economic activities of women in 1st millennium Babylonia / Yoko Watai -- Beauty experts : female perfume-makers in the 1st millennium BC / Laura Cousin -- Women and prebends in Seleucid Uruk / Julien Monerie -- Women and the economic history of the ancient Greek world : still a challenge for gender studies / Violaine Sebillotte Cuchet